The Biology of Coral Reefs (Biology of Habitats) - Sheppard, Charles R. C. (Oxford University Press, 2012)
Coral reefs represent the most spectacular and diverse marine ecosystem on the planet as well as a critical source of income for millions of people. However, the combined effects of human activity have led to a rapid decline in the health of reefs worldwide, with many now facing complete destruction.